Structure and wetting properties of metal polymer nanocomposites. (20th May 2009) - Han, Z.J.; Tay, B.K.; Ha, P.C.T.; Shakerzadeh, M.; , G.F. You
Polystyrene thin films of thickness 180-200 nm are modified by plasma immersion ion implantation and deposition (PIII&D) technique together with titanium filtered cathodic vacuum arc. The surface structure of modified films turns into a metal polymer nanocomposite where Ti nanoclusters of spatial size 10-20 nm are embedded in polystyrene matrices. Such structural formation is discussed with the theory of ion-polymer interactions. Furthermore, the wetting properties of this nanocomposite, such as contact angle ageing effect and hysteresis are investigated and compared with Ti deposited polystyrene films.